1993
DOI: 10.1177/019262339302100506
|View full text |Cite
|
Sign up to set email alerts
|

Histopathologic Approaches to Chemical Toxicity Using Primary Cultures of Dissociated Neural Cells Grown in Chamber Slides

Abstract: Morphologic lesions have received only limited attention as in vitro endpoints of toxicity. In the present work, "tissue" and cell morphology of control and toxicant-treated primary dissociated cerebrocortical cell cultures from fetal mice were examined using phase-contrast and bright-field microscopy. In untreated control cultures, a reproducible sequence of developmental events included cellular reaggregation, intercolony bridging with cell migration, and neuronal apoptosis, with maturation yielding confluen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

1995
1995
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 15 publications
1
8
0
Order By: Relevance
“…The antimitotic agents AraC, FdU, and camptothecin were assayed for their abilities to decrease glial contamination in dissociated CST neuron cultures. Although a low concentration of FdU was moderately effective for decreasing glial contamination (data not shown), addition of all of the antimitotics generally decreased cell number, regardless of cell type, as has been previously reported (Bolon et al, 1993; Besirli et al, 2003). Because these antimitotic agents appeared to exert deleterious effects on neuronal survival and outgrowth, they were not included in further experiments (Supp.…”
Section: Resultssupporting
confidence: 81%
“…The antimitotic agents AraC, FdU, and camptothecin were assayed for their abilities to decrease glial contamination in dissociated CST neuron cultures. Although a low concentration of FdU was moderately effective for decreasing glial contamination (data not shown), addition of all of the antimitotics generally decreased cell number, regardless of cell type, as has been previously reported (Bolon et al, 1993; Besirli et al, 2003). Because these antimitotic agents appeared to exert deleterious effects on neuronal survival and outgrowth, they were not included in further experiments (Supp.…”
Section: Resultssupporting
confidence: 81%
“…Activation of JNK and p38 as well as subsequent induction of apoptosis may also contribute to the neurotoxicity of other environmental toxicants. It has become increasingly clear that many toxicants exert their toxic effects by inducing apoptosis (Bolon et al, 1993;Alison and Sarraf, 1995;Bulleit and Cui, 1998). For example, other heavy metals, including lead, mercury, and lithium, all induce neuronal apoptosis (D'Mello et al, 1994;Kunimoto, 1994;Sarafian et al, 1994;Oberto et al, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…Thus the mechanism of malformations observed in various parts of fetal body is not well known. It was reported that injection of Ara-C to pregnant mice induced increased apoptosis of neuroepithelial cells in the fetal telencephalon 9 and Ara-C caused apoptosis in many different cell culture models [10][11][12] . However, due to the lack of reports regarding fetal cell apoptosis induced by transplacental exposure of Ara-C, little is known about the mechanism of fetotoxic effect of Ara-C including its relationship with cytotoxicity, i.e.…”
Section: Introductionmentioning
confidence: 99%